1981
DOI: 10.1111/j.1365-2125.1981.tb01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling theophylline response in individual patients with chronic bronchitis.

Abstract: 1 In six patients with chronic bronchitis, serial changes in both ventilatory function and plasma theophylline concentrations were measured simultaneously for 8 h following 500 mg aminophylline intravenously. 2 Using empirical mathematical models which can integrate this data, parameters were estimated which can express response as a linear function of steady state plasma theophylline levels. 3 Taking Forced Vital Capacity (FVC) as the target response, the mean (+/‐ s.d.) increase in FVC was 0.06 +/‐ 0.02 l/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…[31][32][33][34] The above indicates the bronchodilator with a rapid onset of action and a need for more detailed pharmacokinetic/pharmalong duration of bronchodilatory effect, lasting more codynamic research with these drugs. Furthermore, than 12 h. [1][2][3][4] Theophylline induces a modest shortthe knowledge of possible kinetic and/or dynamic lasting effect in large airways, [5][6][7] and a more prointeractions will be important for optimizing the prenounced effect in peripheral airways. 8,9 scription of both drugs simultaneous.…”
mentioning
confidence: 99%
“…[31][32][33][34] The above indicates the bronchodilator with a rapid onset of action and a need for more detailed pharmacokinetic/pharmalong duration of bronchodilatory effect, lasting more codynamic research with these drugs. Furthermore, than 12 h. [1][2][3][4] Theophylline induces a modest shortthe knowledge of possible kinetic and/or dynamic lasting effect in large airways, [5][6][7] and a more prointeractions will be important for optimizing the prenounced effect in peripheral airways. 8,9 scription of both drugs simultaneous.…”
mentioning
confidence: 99%
“…correlated with serum levels in a classic dose-response relationship. 101 In contrast, in patients with COPD, it is quite impossible to determine concentration-effect Combination therapy with theophylline and another curves to theophylline because the reproducibility of bronchodilator the magnitude of the response is dependent on the It is noteworthy to underline that additive bronfunctional index that has been used, 102,103 although chodilating effects of oral theophylline and inhaled there is evidence of a modest dose-response effect. 104 agents were evident in some studies (Table 5) and for Even when care is taken to ensure a constant serum this reason the role of theophylline in a multidrug concentration, the bronchodilator action is limited in regimen was addressed in a recent review.…”
Section: Comparison Of Anticholinergic Agents and 2 -Agonistsmentioning
confidence: 89%
“…This is not sur prising, since the differences between the mean levels of theophylline reach only ap proximately 2 ug/ml, and are probably not sufficient for inducing a relevant dif ference in ventilatory effect. Whiting et al [9] observed indeed a mean increase in FVC of only 60 ml/ug-ml' 1 theophylline blood level.…”
Section: Discussionmentioning
confidence: 99%